Vive la Différence: A Comparison of Male-Female Academic Performance - Decore, Anne Marie (Canadian Journal of Higher Education, 1984)
The increase in female participation in University education is a trend that has been obvious for some time. On the basis of the literature on intelligence and achievement testing some of which shows males to be superior in mathematical and scientific areas and females to be superior in humanities and social science areas, it might be expected that performance at the university level would reflect these differential strengths. This expectation should be reinforced as the numbers of males and females in given areas of study become more equal and the effects of selection of the "cream of the crop" are reduced, particularly for women in math-sciences. An examination of data on performance at the University of Alberta gives no support for the expectation of superior performance by males in math-science areas of study.